2017
DOI: 10.2214/ajr.16.17219
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Different Staging Systems for Multiple Myeloma: Can the MRI Pattern Play a Prognostic Role?

Abstract: These data indicate that both the International Staging System and the Durie-Salmon PLUS system have great potential for characterizing and stratifying MM to determine the survival outcome and therapy response of patients. Observation of a focal pattern on MRI seems to be associated with poorer survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 23 publications
2
11
0
2
Order By: Relevance
“…It is believed that DS Plus is a reliable method for both staging and prognostic classification. The prognostic significance of DS Plus has been reported in one recent study using MRI of the spine and pelvis in 85 patients [ 27 ]. However, Fechtner et al have reported that the DS Plus is not better than the DSS for the prediction of OS [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that DS Plus is a reliable method for both staging and prognostic classification. The prognostic significance of DS Plus has been reported in one recent study using MRI of the spine and pelvis in 85 patients [ 27 ]. However, Fechtner et al have reported that the DS Plus is not better than the DSS for the prediction of OS [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][60][61][62][63] This is probably one of the reasons for discrepant results in the literature as to which MRI pattern confers a worse prognosis in patients with newly diagnosed MM. [64][65][66] Moreover, the diffuse pattern (as opposed to the focal pattern) has not been incorporated in the updated criteria for the diagnosis of symptomatic myeloma. 43 WBDWI has been shown to be more sensitive than fluorodeoxyglucose PET-CT in detecting diffuse disease, by visually assessing the inverted grayscale maximum intensity projection images with b-value 800-900 s mm -2 .…”
Section: Whole Body Mri and Whole Body Diffusionweighted Imagingmentioning
confidence: 99%
“…The updated Durie-Salmon PLUS system for MM staging, which was found to be determinative of treatment response and survival outcome incorporates lesion quantification from whole body imaging survey in addition to serum biomarkers (11). Historically the Mirels score on conventional radiography (CR) predicted risk of fracture and guided to select between radiotherapy or preventive osteosynthesis as an intervention in patients with MM (12).…”
Section: Transmission Imaging Modalities For Multiple Myeloma Work-upmentioning
confidence: 99%